Answer:
See below both methods.
Explanation:
9x + 6y = 18
-6x - 6y = -24
Elimination:
9x + 6y = 18
-6x - 6y = -24
Since 6y and -6y add to zero, add the equations to eliminate y and solve for x.
9x + 6y = 18
(+) -6x - 6y = -24
-------------------------
3x = -6
x = -2
Now we need to eliminate y and solve for x. Divide both sides of the second equation by 6 and multiply both sides of the second equation by 9 to get this new equation.
-9x - 9y = -36
Add this new equation to the first original equation to eliminate x.
9x + 6y = 18
(+) -9x - 9y = -36
-------------------------
-3y = -18
y = 6
Solution: x = -2; y = 6
Substitution:
9x + 6y = 18
-6x - 6y = -24
Divide both sides of the first equation by 3. Divide both sides of the second equation by -6.
3x + 2y = 6 (Equation 1)
x + y = 4 (Equation 2)
Solve the second equation for x.
x = 4 - y
Substitute 4 - y for x in Equation 1 and solve for y.
3(4 - y) + 2y = 6
12 - 3y + 2y = 6
-y + 12 = 6
-y = -6
y = 6
Now substitute 6 for y in equation 2 and solve for x.
x + 6 = 4
x = -2
Solution: x = -2, y = 6